Indonesian Coffee Diplomacy in Strengthening Bilateral Relations Between Indonesia and Kazakhstan in 2019-2024 - Wijaya, Nadia Puspita; Fathun, Laode Muhamad (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
Indonesia has many types of coffee that can be exported abroad. Coffee is one of Indonesia's export products that can enter Kazakhstan, a country similar to Indonesia. Both are countries with a Muslim majority. This multicultural country in Central Asia has experienced increasing growth in coffee shops since 2019-2020. Central Asia is a target for Indonesia's economic diplomacy because it has the potential to increase exports and investment. Kazakhstan's strategic position as a trade and business center in Central Asia means that this country will re-export coffee to surrounding countries, namely Kyrgyzstan, Uzbekistan, and Mongolia. Researchers are interested in seeing how Indonesia’s coffee diplomacy strategy improves bilateral relations between Indonesia and Kazakhstan because there has been no research on Indonesia’s coffee diplomacy with Kazakhstan. The research was conducted using qualitative research methods, such as collecting primary data through interviews and observations and secondary data through literature reviews from articles, journals, books, video documentation, and publication documentation. Researchers have observed Kazakhstan and see that Indonesian coffee products are attractive and suitable for foreigners and local Kazakhs. The Embassy of the Republic of Indonesia in Astana promotes coffee by displaying Indonesian coffee products at the Indonesian Cultural Center and displaying or bringing coffee products to various state events, approaching or lobbying the market or distributors, and establishing agreements in terms of policy.